Teachers’ Assessment Approaches Regarding EFL Students’ Speaking Skill - Jaime Fernando Duque-Aguilar (Profile: Issues in Teachers' Professional Development)
This paper reports an exploratory and descriptive qualitative study on speaking assessment approaches in a teacher education program at a Colombian university. The study aimed to explore how four in-service English language teachers approach the assessment of students’ speaking skill. The data were gathered through classroom observations, interviews, and documentary analysis. Results revealed teachers’ preference for summative assessment practices to determine students’ progress regarding speaking. As a conclusion, teacher professional development in terms of language assessment may be seen as an alternative to develop significant assessment processes where students, teachers, and the institution can be benefited.